FEATURES OF GENOTYPiNG VARIABILITY OF STRAINS OF BORDETELLA PERTUSSIS ALLOCATED FROM PATIENTS WITH WHOOPING COUGH IN RUSSIA - V. A. Aleshkin; O. Yu. Borisova; N. T. Gadua; I. K. Mazurova (Acta Biomedica Scientifica)
On the basis of studying of features of structure of 7 genes determining major factors of pathogenicity of the causative agent of whooping cough - ptxA, ptxB, ptxC, ptxD, ptxE, ptxP and prn, features of genotyping variability of strains of B.pertussis allocated from patients with whooping cough in Russia are shown. Dynamics of formation of population of strains of the causative agent of whooping cough is tracked and is established that population of strains of B.pertussis is formed by clonal expansion of strains with, new genetic structure of major factors of pathogenicity - pertussis toxin and. pertactin. The structure of population of strains of B.pertussis causing a disease by whooping cough, at the present stage of epidemic process of a pertussis infection - domination. of strains with new «non-vaccine» alleles genes - ptxA1 (97,7 %), ptxC2 (87,4 %), prn2 (89,5 %) and. ptxP3 (93,3 %), in 2,2 % cases with ptxB2 allele and. in 1,3 % cases with. prn9 allele circulate.